2012
DOI: 10.1103/physrevb.86.115203
|View full text |Cite
|
Sign up to set email alerts
|

Thermal conductivity of diamond under extreme pressure: A first-principles study

Abstract: Using a first principles approach based on density functional perturbation theory and an exact numerical solution to the phonon Boltzmann equation, we show that application of large compressive hydrostatic pressure dramatically increases the thermal conductivity of diamond.We connect this enhancement to the overall increased frequency scale with pressure, which makes acoustic velocities larger and reduces phonon-phonon scattering rates. Of particular importance is the often neglected fact that heat-carrying ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
83
4
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 118 publications
(95 citation statements)
references
References 55 publications
7
83
4
1
Order By: Relevance
“…Moreover, unlike the work of Ref. 28, we find qualitatively uniform dependences of k on strain from the full BPE solution and the SMRTA, consistent with that found in strained 3D diamond [40]. Unless specified otherwise, all the results shown below are for N 1 =301 for unstrained and strained is due partly to decreasing magnitude of the anharmonic IFCs with tensile strain [23], which reduces the scattering matrix elements, and partly to the reduction in ZA phonon density of states caused by zone center dispersion linearization [22], which leads to less scatterings of ZA phonons [18].…”
Section: Introductionsupporting
confidence: 67%
See 1 more Smart Citation
“…Moreover, unlike the work of Ref. 28, we find qualitatively uniform dependences of k on strain from the full BPE solution and the SMRTA, consistent with that found in strained 3D diamond [40]. Unless specified otherwise, all the results shown below are for N 1 =301 for unstrained and strained is due partly to decreasing magnitude of the anharmonic IFCs with tensile strain [23], which reduces the scattering matrix elements, and partly to the reduction in ZA phonon density of states caused by zone center dispersion linearization [22], which leads to less scatterings of ZA phonons [18].…”
Section: Introductionsupporting
confidence: 67%
“…Fig.1(a) for which the boundary scattering is neglected totally. Interestingly, the tensile-strain-induced enhancement of k is in contrast to those reported for other carbon-based materials such as 3D diamond [40] and 1D carbon nanotubes [30,45], wherein tensile strains reduce k through phonon softening [45]. While the softening of LA, TA and optic phonons in graphene is indeed observed here, we find hardening of the ZA modes, i.e., higher ZA frequencies and low-frequency group velocities for the strain levels considered.…”
Section: Introductioncontrasting
confidence: 54%
“…Similar behavior has been previously noted in Si and Ge [7,30]. For systems with very strong N scattering relative to U scattering, such as in diamond [9][10][11], graphene [31,32] and carbon nanotubes [22,33], the full solution to the BTE is required to accurately determine κ L .…”
Section: Thermal Transport and Anharmonic Ifcsmentioning
confidence: 73%
“…We found that including only 1 st nearest neighbors required very large changes to the anharmonic IFCs in order to enforce the TI conditions and thus was not included here. We have also used a reciprocal-space DFPT approach (black dashed curve) to calculate the anharmonic IFCs and to calculate κ natural , which extends the interactions to 7 th nearest neighbors and includes long range Coulomb interactions [7,[9][10][11][49][50]. As can be seen in Figure 3, the calculated κ natural is fairly insensitive to the nearest neighbor cut-off radius.…”
Section: Test Cases (Si Ge and Gaas)mentioning
confidence: 99%
See 1 more Smart Citation